Lower socioeconomic status is independently associated with shorter survival in Hodgkin Lymphoma patients—An analysis from the Brazilian Hodgkin Lymphoma Registry. Issue 5 (26th October 2017) - Biasoli, Irene; Castro, Nelson; Delamain, Marcia; Silveira, Talita; Farley, James; Pinto Simões, Belinda; Solza, Cristiana; Praxedes, Monica; Baiocchi, Otávio; Gaiolla, Rafael; Franceschi, Fernanda; Bonamin Sola, Caroline; et al.
Abstract : Socioeconomic status (SES) is a well‐known determinant of outcomes in cancer. The purpose of this study was to analyze the impact of the SES on the outcomes of Hodgkin lymphoma (HL) patients from the Brazilian Prospective HL Registry. SES stratification was done using an individual asset/education‐based household index. A total of 624 classical HL patients with diagnosis from January/2009 to December/2014, and treated with ABVD (doxorubicin, bleomycin, vinblastine and dacarbazine), were analyzed. The median follow‐up was 35.6 months, and 33% were classified as lower SES. The 3‐year progression‐ free survival (PFS) in higher and lower SES were 78 and 64% ( p  < 0.0001), respectively. The 3‐year overall survival (OS) in higher and lower SES were 94 and 82% ( p  < 0.0001), respectively. Lower SES patients were more likely to be ≥ 60 years (16 vs . 8%, p  = 0.003), and to present higher risk International Prognostic score (IPS) (44 vs . 31%, p  = 0.004) and advanced disease (71 vs . 58%, p  = 0.003). After adjustments for potential confounders, lower SES remained independently associated with poorer survival (HR = 3.12 [1.86‐5.22] for OS and HR = 1.66 [1.19‐2.32] for PFS). The fatality ratio during treatment was 7.5 and 1.3% for lower and higher SES ( p  = 0.0001). Infections and treatment toxicity accounted for 81% of these deaths. SES is an independent factor associated with shorter survival in HL in Brazil. Potential underlying mechanisms associated with the impact of SES are delayed diagnosis and poorer education. Educational and socio‐economic support interventions must be tested in this vulnerable population. Abstract : What's new? While the outcome of Hodgkin's lymphoma (HL) has markedly improved over the last decades, substantial disparities persist in large areas of the world. This study found that HL patients with a lower socio‐economic status (SES) in Brazil, a country of extreme wealth inequality, were more likely to present with advanced disease and poor prognostic features. SES was independently associated with shorter survival. Deaths during treatment were more common in patients with a lower SES, mostly due to infections. Potential underlying mechanisms are delayed diagnosis and poorer education, highlighting educational and socio‐economic support interventions as potentially beneficial in this vulnerable population.